Perasan Daun Pepaya (Carica papaya L.) sebagai Pengendali Infestasi Argulus pada Ikan Komet (Carassius auratus auratus) [ Papaya Leaf Juice (Carica papaya L.) For Control Infestation Of Argulus At Comet Fish (Carassius auratus auratus) ] - Kismiyati Kismiyati; Puput Puspitasari; Laksmi Sulmartiwi (Jurnal Ilmiah Perikanan dan Kelautan, 2012)
Abstract Comet fish farming are very popular almost all over Indonesia. Production problems associated with cultivation can not be separated from discussions about the disease that can cause death in fish. One of the parasites known to infect comet fish is Argulus. One alternative to the safe control of ectoparasites is to use papaya leaves. The content of the papaya leaves one of them is an alkaloid carpain. The purpose of this study was to determine which the juice of papaya leaves (Carica papaya L.) can release Argulus that infest comet fish (Carassius auratus auratus) and the concentration of papaya leaf juice is effective as a control Argulus that infest comet fish. The method used is an experimental laboratory with a Completely Randomized Design (CRD) as an experimental design. The treatments used were is the concentration of the difference papaya leaf juice, A (0%), B (20%), C (25%) and D (30%) with five replications. The main parameters of the observed loss of Argulus is attached to the comet fish and behavior of comet fish. Observations include water quality parameters include temperature, pH, and dissolved oxygen. Analysis of data by using ANOVA test (Analysis of Variance),if there is a difference among treatments, followed by Duncan's Multiple range test. The result showed ANOVA test with p <5% indicates that the soaking juice of papaya leaves Argulus infestations affect the comet fish. The best juice of papaya leaves is treatment D (30%) which can move 88% in immersion for 20 minutes.